Dental professionals' perception of their role in the practice of oral health promotion: a qualitative interview study - Elena Shmarina; Dan Ericson; Bengt Götrick; Cecilia Franzén (BMC, 2023)
Abstract Objective To explore dental professionals' perceptions of their role in the practice of oral health promotion. Material and method In-depth interviews were conducted with three dentists, one specialist dentist and seven dental hygienists. All were employed in the public dental service in Kalmar County, Sweden and had at least 2 years' work experience. The interview questions addressed the experience and views of dental professionals with reference to their role in the practice of health promotion. The interview data were subjected to qualitative content analysis. Results Analysis revealed two themes which capture the essence of the dental professionals' perception of their role in the practice of oral health promotion. One theme, having person-focused approach, comprised four categories: 'considering the patient's life situation', 'establishing a trusting relationship with patients', 'strengthening patients' commitment to oral health' and 'health education'. The other theme, perceiving social responsibility for oral health, comprised three categories: 'dissemination of oral health knowledge', 'interprofessional collaboration' and 'equality in oral health care'. Conclusion Dental professionals perceived promotion of oral health to be an important aspect of their professional role. They aspired to patient participation in the decision-making process and educational activities, as well as practising and evaluating skills development. Although the dental professionals perceived that they undertook health promotion activities, they did not clearly distinguish between oral health promotion and disease prevention. There was intra- and inter-professional agreement among the dentists and dental hygienists with respect to expected outcomes for health promotion activities.